2023
DOI: 10.3847/1538-4357/acdeec
|View full text |Cite
|
Sign up to set email alerts
|

Circumgalactic Medium on the Largest Scales: Detecting X-Ray Absorption Lines with Large-area Microcalorimeters

Ákos Bogdán,
Ildar Khabibullin,
Orsolya E. Kovács
et al.

Abstract: The circumgalactic medium (CGM) plays a crucial role in galaxy evolution as it fuels star formation, retains metals ejected from the galaxies, and hosts gas flows in and out of galaxies. For Milky Way–type and more-massive galaxies, the bulk of the CGM is in hot phases best accessible at X-ray wavelengths. However, our understanding of the CGM remains largely unconstrained due to its tenuous nature. A promising way to probe the CGM is via X-ray absorption studies. Traditional absorption studies utilize bright … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Nelson et al (2023a) investigated the possibility that the resonant scattering of O VIIr emission line photons could boost the CGM signal from this line to be significantly brighter than the intrinsic emission alone, using galaxies from the the Illustris TNG50-1 (hereafter TNG50) simulations. Bogdan et al (2023) showed using mock LEM observations of galaxies from the Magneticum simulations that O VII and O VIII absorption lines can be detected at very large radius. Comparisons between galaxies from Illustris "The Next Generation" (TNG), SIMBA, and EAGLE demonstrate that emission lines from oxygen and iron in the X-ray band can be used to distinguish between different models of AGN feedback and determine the role of feedback from supernovae and black holes in regulating star formation (Truong et al 2023b).…”
Section: Introductionmentioning
confidence: 99%
“…Nelson et al (2023a) investigated the possibility that the resonant scattering of O VIIr emission line photons could boost the CGM signal from this line to be significantly brighter than the intrinsic emission alone, using galaxies from the the Illustris TNG50-1 (hereafter TNG50) simulations. Bogdan et al (2023) showed using mock LEM observations of galaxies from the Magneticum simulations that O VII and O VIII absorption lines can be detected at very large radius. Comparisons between galaxies from Illustris "The Next Generation" (TNG), SIMBA, and EAGLE demonstrate that emission lines from oxygen and iron in the X-ray band can be used to distinguish between different models of AGN feedback and determine the role of feedback from supernovae and black holes in regulating star formation (Truong et al 2023b).…”
Section: Introductionmentioning
confidence: 99%